ANALISIS KEBIJAKAN PEMERINTAH TERHADAP PENGANUT AGAMA BAHA’I DI KABUPATEN PATI, PROVINSI JAWA TENGAH - Nuhrison M Nuh (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This study employs the analytical descriptive research that explores in-depth information about the existence of Baha’i religion in Indonesia that many societies have not known about it. The study describes phenomenon and facts about Baha’i religion. The data collection consists of literature study, document analysis, in-depth interview, and observation. The study that is conducted in Cebolek village, Margoyoso district, Pati aims to know the Baha’i history, main teachings, and adherents as well their spread; find the implementation of government policy to fulfill Baha’i adherents’ right; to figure out the social relationship between Baha’i adherents and their society around them. The results of study show that Baha’i quite exists in Cebolek village, Margoyoso district, Pati even though it has not developed, less than 23 people; Baha’i adherents have their rights in obtaining services though in fact there are some changes; their social relationship with their society is good because they behave politely and they are active in some activities in their social environment.